법랑질 표면 처리방법에 따른 레진계 치아 고정재료의 접착강도 비교 - 이예림(Ye-Rim Lee); 김수연(Soo-Yeon Kim); 김진우(Jin-Woo Kim); 박세희(Se-Hee Park); 조경모(Kyung-Mo Cho) (Journal of dental rehabilitation and applied science, 2019)
Purpose: The purpose of this study is to compare and analyze the shear bond strength and fracture pattern in different enamel tooth surface treatments for resin splinting materials. Materials and Methods: G-FIX and LightFix were used as tooth splinting materials. Twenty bovine mandibular incisors were used for the preparation of the specimens. The exposed enamel surface was separated into four parts. Each tooth was treated with 37% phosphoric acid, 37% phosphoric acid + adhesive resin, 37% phosphoric acid + G-premio bond, and G-premio bond for each fraction. Shear bond strength was measured using a universal testing machine. After measuring the shear bond strength, the fractured surface of the specimen was magnified with a microscope to observe the fracture pattern. Two-way ANOVA was used to verify the interaction between the material and the surface treatment method. One-way ANOVA was used for comparison between the surface treatment methods of each material and post-hoc test was conducted with Scheffe's test. An independent t-test was conducted to compare shear bond strengths between materials in each surface treatment method. All statistics were conducted at 95% significance level. Results: G-FIX, a tooth splinting resin, showed similar shear bonding strength when additional adhesive resins were used when material was applied after only acid etching, and LightFix showed the highest shear bonding strength when additional adhesive resins were used after the acid etching. In addition, both G-FIX and LightFix showed the lowest shear bond strength when only self-etching adhesive was applied without additional acid etching. Verification of interactions observed interconnection between resins and surface treatment methods. Most of the mixed failure was observed in all counties. Conclusion: When using G-FIX and LightFix, which are tooth-splinting materials, it is considered that sufficient adhesion will be achieved even after applying only acid etching as instructed by the manufacturer. 목적: 본 연구의 목적은 레진계 치아고정 재료의 법랑질 치면 처리 방법에 따른 전단결합강도와 파절 양상을 비교 분석하는 것이다. 연구 재료 및 방법: 레진계 치아고정 재료로 G-FIX, LightFix를 사용하였다. 시편 제작을 위해 소의 하악 절치 20개를 사용했다. 노출된 법랑질 표면을 4부분으로 구분하여, 각 분획 마다 37% 인산(E), 37% 인산+Adhesive resin (E+A), 37% 인산+G-premio bond (E+GP), G-premio bond (GP)로 각각의 치면 처리를 하고, 재료를 접착하였다. 만능 시험기를 이용하여 전단결합강도를 측정하였고, 시편의 파절된 표면을 현미경으로 확대하여 파절 양상을 관찰하였다. Two-way ANOVA를 이용하여 재료와 표면처리 방법 사이의 상호작용을 검증하였고 각 재료에서 표면처리 방법 사이의 비교를 위해 One-Way ANOVA test를 하고 Scheffe's test로 사후 검정 하였다. 각 표면처리 방법에서 재료 사이의 전단결합강도를 비교하기 위해 independent t-test를 하였다. 모든 통계는 95% 유의수준에서 진행하였다. 결과: 동요치 고정을 위한 G-FIX는 산부식만 시행한 후 재료를 적용해도 접착 레진을 추가적으로 사용했을 때와 유사한 전단결합강도를 보였으며 LightFix는 산부식을 시행한 후 접착 레진을 추가적으로 사용했을 때 가장 높은 전단결합강도를 보였다. 또한, G-FIX와 LightFix 모두에서 별도의 산부식 없이 자가부식 접착제만 처리했을 때 가장 낮은 전단결합강도를 보였다. 교호작용의 검증 결과 치아고정용 레진과 표면처리 방법 사이의 상호 연관됨이 관찰되었다. 파절 양상은 모든 군에서 대부분 혼합성 파절이 관찰되었다. 결론: 치아 고정용 레진인 G-FIX와 LightFix의 사용시 제조사의 지시와 같이 산부식만 시행한 후 재료를 적용해도 충분한 접착이 이루어질 것으로 생각된다.